Dragons in the waters - L'Engle, Madeleine (Laurel-leaf books, 1982)
A thirteen-year-old boy's trip to Venezuela with his cousin culminates in murder and the discovery of an unexpected bond with an Indian tribe, dating from the days of Simón Bolívar.